Indonesian Teachers Technique in Teaching English at Chariyatham Suksa Foundation School, Chana, Songkhla, Thailand - Khoiri Khoiri; Leffi Noviyenty; Sarwo Edy (Journal of English Education and Teaching, 2019)
This thesis was aimed to find out teachers’ techniques in teaching English and teachers’ problems at Chariyatham Suksa Foundation School. This research was mixed- method which presented in descriptive way to describe it. Teachers from Indonesia who thought in secondary school are conducted informants or subject of this study and the last year students of secondary school of Chariyatham Suksa Foundation School are participants in this research. The researcher used observation, interview and questionnaire to get data that needed. In analysis data, first researcher identifies and checks data that be collected. After that, researcher describes all data that got. Next, researcher classifies data into categories based on research instrument and the last is interpret the data which gotten. The findings revealed that in teaching English. The teacher A used and implemented games, organizational, dialogue/narrative presentation and reading aloud techniques. Then teacher B used and implemented warm up, content explanation, brainstorming, checking, question-answer display technique. Meanwhile, teacher A got problem in lack of interest, lack of concentration in the class, lack of repetition and frequent practice of students, insufficient time, recourse and material and students is defiant, rowdy, or distracting of other. then teacher B got problem on lack of concentration in the class, lack of repetition and frequent practice of the students and Insufficient Time, Resource and Materials.